Analyzing Media Bias in Support of Government Policies: A Critical Discourse Analysis in a Newspaper - Agung Farid Agustian (PAROLE: Journal of Linguistics and Education, 2025)
The newspaper media demonstrates clear support for the current government, as revealed in a study that addresses the negative impacts of media bias and raises awareness of biased media agendas. Van Dijk's Critical Discourse Analysis (CDA) shed light on how social, political, and ideological contexts influence the production and interpretation of texts. The study focused on a Jakarta Post news article published on oil hike price on Saturday, September 3, 2022e. Through a descriptive qualitative analysis using CDA, the study examined the news text's macrostructure, superstructure, and microstructure, uncovering significant bias. The Jakarta Post's coverage presented a skewed perspective on the government's decision to raise fuel prices, acknowledging social and political implications, including the potential for public unrest and concerns about corrupt power.